Intention and Moral Enhancement. (30th September 2016) - Simkulet, William
Abstract: Recently philosophers have proposed a wide variety of interventions referred to as 'moral enhancements'. Some of these interventions are concerned with helping individuals make more informed decisions; others, however, are designed to compel people to act as the intervener sees fit. Somewhere between these two extremes lie interventions designed to direct an agent's attention either towards morally relevant issues – hat‐hanging – or away from temptations to do wrong – hat‐hiding. I argue that these interventions fail to constitute genuine moral enhancement because, although they may result in more desirable outcomes – more altruism, more law‐following, and/or less self‐destructive behavior, they ignore a person's intentions, and often what makes an action right or wrong is the intent behind it.